PENGARUH ACTIVE KNOWLEDGE SHARING TERHADAPKEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA - Nurdiana, Aty; Haryanto, Haryanto (Lentera: Jurnal Ilmiah Kependidikan, 2019)
The purpose of this study was to determine the effect of Active Knowledge Sharing learning strategies on mathematical communication skills of seventh grade students in the middle semester of Middle S 1 Sungkai. The method used in this study is the experimental method by conducting research directly using the Active Knowledge Sharing strategy in the experimental class and conventional learning in the control class. The population in this study were all students of class VIII Even Semester 1 of South Sungkai Middle School which consisted of 5 classes with a total of 208 students, while the sample was taken by two classes namely class VIII.2 as the experimental class, and class VIII 3 as the control class. Then the two classes were given a test in the form of an essay test of 5 questions which were first tested for validity and reliability. Hypothesis testing in this study using the t-test formula with the value t=6.16 and from the distribution table t at a significant level of 5% it is known that t=1.99, t> tso that it can be concluded that "There is an influence of the application of Active Knowledge Sharing learning to mathematical communication skills of eighth grade students of the semester of South Sungkai 1 Middle School 2017/2018 school year"